An exploration into the relationship between brand and industry evolution - Marks, Helen J. (Trinity College (Dublin, Ireland). Trinity Business School, 2015)
There is still much to discover about the evolution of whole industries, their boundaries and the influence of the final consumer on the products and services industries create. Brands have become integral to the contemporary customer decision-making process yet despite suggestions that they influence industry level change there is a paucity of empirical research to support or explain this hypothesis. This was the motivation for the study. Through analysing the agency of brand over extended periods of time, irrespective of the material assets they complement, an opportunity existed to build a conceptual basis to explicate how brands influence change and justify brand’s centrality to business strategy.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin